2020
DOI: 10.1186/s12935-020-01689-8
|View full text |Cite
|
Sign up to set email alerts
|

RRM2 protects against ferroptosis and is a tumor biomarker for liver cancer

Abstract: Background Ferroptosis is the process of cell death triggered by lipid peroxides, and inhibition of glutathione (GSH) synthesis leads to ferroptosis. Liver cancer progression is closely linked to ferroptosis suppression. However, the mechanism by which inhibition of GSH synthesis suppresses potential ferroptosis of liver cancer cells and whether ferroptosis-related liver cancer biomarkers have a promising diagnostic value remain unknown. Methods Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 76 publications
(101 reference statements)
2
85
0
Order By: Relevance
“…So far, there are no specific markers of ferroptosis as a cell death mechanism and because we were exploring the non-lethal effect of ferroptosis, in this work we evaluated the levels of ROS-induced lipids peroxides underlying ferroptosis and GSH dynamics (67). The expression of genes pointed as being decreased upon ferroptosis activation, PTGS2, GPX4 and GSS was also assessed (10,(68)(69)(70). In our experimental conditions, we observed that Erastin significantly decreases cyst(e)ine uptake (Figure 1E) and promotes the increase of intracellular ROS (Figure 1A) and lipid peroxide levels (Figure 1C), without affecting the mitochondrial ROS content (Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are no specific markers of ferroptosis as a cell death mechanism and because we were exploring the non-lethal effect of ferroptosis, in this work we evaluated the levels of ROS-induced lipids peroxides underlying ferroptosis and GSH dynamics (67). The expression of genes pointed as being decreased upon ferroptosis activation, PTGS2, GPX4 and GSS was also assessed (10,(68)(69)(70). In our experimental conditions, we observed that Erastin significantly decreases cyst(e)ine uptake (Figure 1E) and promotes the increase of intracellular ROS (Figure 1A) and lipid peroxide levels (Figure 1C), without affecting the mitochondrial ROS content (Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione synthetase (GSS), which plays a key role in metabolism, catalyzes the last step of glutathione (GSH) synthesis, which is an important antioxidant that protects cancer cells against potential ferroptosis ( Proneth and Conrad, 2019 ; Chen et al, 2020 ). In liver cancer, researchers found that RRM2 was capable of sustaining intracellular GSH by protecting GSS from degradation ( Yang et al, 2020 ). To the best of our knowledge, this is the first study to explore the correlation between the expression of GSS and the carcinogenic environment of UVM.…”
Section: Discussionmentioning
confidence: 99%
“…As for the top ten hub Fer-MRGs, few studies have investigated their role in ferroptosis, while RRM2 has been identified as an anti-ferroptotic regulator in HCC by promoting the GSH synthesis in a recent study. 23 Hence, these findings need further investigation.…”
Section: Discussionmentioning
confidence: 94%
“… 24 , 25 RRM2 has been found a role in GSH synthesis and ferroptosis inhibition in HCC. 23 Besides, RRM2 was also found as a core gene in the p53 regulation pathway in hepatitis B virus-related HCC. 26 TXNRD1 was identified as a key metabolic reprogramming-associated gene, and could participate in the regulation of oxidative stress and lipid peroxidation in HCC.…”
Section: Discussionmentioning
confidence: 99%